INVENTARISASI STATUS KEANEKARAGAMAN HAYATI SEBAGAI BASELINE UPAYA PERLINDUNGAN KEANEKARAGAMAN HAYATI DALAM PENILAIAN PROPER (Studi Kasus: Hutan Kota Telagasari, Kota Balikpapan) - Filson Maratur Sidjabat; Kania Dewi; Deri Ramdhani (Journal of Environmental Engineering and Waste Management, 2017)
Environmental Management effort in conservation will be required to diverse natural resources value, and as a form of favouring the sustainability of biological natural resources and its ecosystem utilization in City Forest of Telagasari (HKTs). HKTs have been designated as a green open space and it is developed as a protected area and education center of biodiversity in Balikpapan City. Data collection was done by direct observation method on terrestrial fauna and flora. There are 133 kind of flora in HKTs (11 flora are protected by IUCN and 14 flora are  protected by PP RI in SK/54/Pertanian/1972) with a Shannon-Wiener Index (H’) 3.04 for ‘semai’ category, 3.02 for ‘pancang’, 3.02 for ‘tiang’, and 1.86 for ‘pohon’ category. The numbers of avifauna that had been recorded in city forest of Telagasari are 35 species (7 has important protection status), with a Shannon-Wiener Index (H’) of 2.762. The numbers of mammals that had been recorded in city forest of Telagasari are 7 species and 21 individuals, with H’ mammals of 1.5. This inventory data and information can be used to support the conservation, as an environmental management effort. The baseline of biodiversity and conservation status in HKTs Balikpapan will be measured as a key parameter for the implementation of biodiversity protection program. The strategic planning and program that are proposed for next fifth year for HKTs may give a positif impact for biodiversity and conservation in HKTs.